Modulation of intracellular kinase signaling to improve TIL stemness and function for adoptive cell therapy. (26th August 2022) - Feng, Hao; Qiu, Ling; Shi, Zixiao; Sheng, Yao; Zhao, Peipei; Zhou, Di; Li, Fei; Yu, Hailin; You, Yanan; Wang, Hui; Li, Ming; Zhu, Shurong; et al.
Abstract: Introduction: Adoptive cellular therapy with tumor‐infiltrating lymphocytes (TIL) has demonstrated promising clinical benefits in several solid tumors, but the efficacy of this therapy might be compromised by the "prone‐to‐exhaustion" phenotype of TIL and poor persistence in vivo. This calls for a robust expansion process to produce a large number of cells for clinical usage while at the same time maintaining favorable anti‐tumor function and memory phenotype. Previous studies showed that the PI3K‐AKT signaling pathway plays a key role in the regulation of T cell activation, differentiation and memory formation. Method: We modulated the PI3K‐AKT pathway in TIL isolated from cervical and ovarian cancer by application of AKT or PI3K inhibitors or CRISPR knockout of AKT1 and/or AKT2, and characterized their effects on TIL phenotype and effector function. Mechanistic study was further performed with RNA‐seq analysis of AKT1/2 KO TIL in comparison to control TIL. Result: The inhibition of either PI3K or AKT led to an increase in the population of effector CD8 + T cells with upregulation of activation markers, elevated CD39 − CD69 − memory T cells, and significantly enhanced cytotoxicity when cocultured with tumor cell lines and patient‐derived tumor samples. Moreover, dual knockout of AKT1 and AKT2 largely phenocopies the functional impact of AKT or PI3K inhibition on TIL. This result was further validated by RNA‐seq analysis indicating that AKT1/2 ablation primarily regulates T cell differentiation and function‐related programs. Conclusion: Modulation of PI3K‐AKT signaling represents a promising strategy to enhance TIL stemness and cytotoxicity and improve the clinical outcome of current TIL‐based therapy to treat solid tumors. Abstract : The PI3K‐AKT pathway in TIL was modulated by AKT or PI3K inhibitors or CRISPR knockout of AKT1 and/or AKT2. The inhibition of either PI3K or AKT led to an increase in the population of effector CD8+ T cells with upregulation of activation marker, elevated CD39CD69 memory T cells, and significantly enhanced cytotoxicity when cocultured with tumor cell lines and patient‐derived tumor samples. The results indicating that modulation of PI3K‐AKT signaling represents a promising strategy to enhance TIL stemness and cytotoxicity and improve the clinical outcome of current TIL‐based therapy to treat solid tumors.